Manfaat Sertifikat Induksi Bagi Guru Pemula untuk Kenaikan Pangkat - Faisal, Muhammad (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
The teacher plays a central role in every learning process. Apart from being a teacher, teachers are also required to be able to be innovators, facilitators, and motivators. The ability of teachers to present learning so that it becomes exciting and fun will determine students' success. Therefore, the Beginner Teacher Induction Program is essential to implement as a means to improve teacher competence. The implementation of the induction PIGP (Program Induksi Guru Pemula) aims to guide novice teachers to adapt to the work climate and culture of the school/madrasah. Thus, after the activity, it is hoped that every teacher can have good pedagogical, professional, social, and personal competence.